Current strategies, advances, and challenges in multi-epitope subunit vaccine development for African swine fever virus - Ella Mae Joy S. Sira; Edward C. Banico; Lauren Emily Fajardo; Nyzar Mabeth O. Odchimar; Alea Maurice Simbulan; Fredmoore L. Orosco (Veterinary Integrative Sciences)
African Swine Fever (ASF), a highly contagious and lethal viral disease affecting swine populations, presents a critical global threat with no approved vaccine. Traditional approaches such as whole virus-based vaccines have several limitations, prompting interest in peptide-based subunit vaccines. However, the inefficacy of existing peptides and the complexity of the ASFV genome further complicate antigen screening. Immunoinformatics has addressed this challenge by utilizing bioinformatics tools for the design and evaluation of multi-epitope subunit vaccines. Although multi-epitope subunit vaccines offer safety advantages, their potential to induce both humoral and cellular immune responses is crucial for protective immunity against ASFV infection. Despite the growing interest in computational vaccine design, a notable gap exists in in vivo confirmation studies. This review addresses the challenges and advances in ASFV multi-epitope subunit vaccine development, underlining the urgency of a safe and effective vaccine given ASF's global impact on swine populations and associated economic losses.